Centaur antibodies: Engineered chimeric equine-human recombinant antibodies - Rosenfeld, Ronit; Alcalay, Ron; Zvi, Anat; Ben-David, Alon; Noy-Porat, Tal; Chitlaru, Theodor; Epstein, Eyal; Israeli, Ofir; Lazar, Shirley; Caspi, Noa; Barnea, Ada; Dor, Eyal; et al. (Frontiers in Immunology, 2022)
Hyper-immune antisera from large mammals, in particular horses, are routinely used for life-saving anti-intoxication intervention. While highly efficient, the use of these immunotherapeutics is complicated by possible recipient reactogenicity and limited availability. Accordingly, there is an urgent need for alternative improved next-generation immunotherapies to respond to this issue of high public health priority. Here, we document the development of previously unavailable tools for equine antibody engineering. A novel primer set, EquPD v2020, based on equine V-gene data, was designed for efficient and accurate amplification of rearranged horse antibody V-segments. The primer set served for generation of immune phage display libraries, representing highly diverse V-gene repertoires of horses immunized against botulinum A or B neurotoxins. Highly specific scFv clones were selected and expressed as full-length antibodies, carrying equine V-genes and human Gamma1/Lambda constant genes, to be referred as “Centaur antibodies”. Preliminary assessment in a murine model of botulism established their therapeutic potential. The experimental approach detailed in the current report, represents a valuable tool for isolation and engineering of therapeutic equine antibodies.